MATERNAL PRACTICES AND THE USE OF ALTERNATIVE THERAPIES IN THE CARE OF THE CHILD - Karina Jullyana de Melo Brondani; Rosângela Aparecida Pimenta Ferrari; Alexandrina Aparecida Maciel Cardelli; Mauren Teresa Grubisich Mendes Tacla; Flávia Genovesi Fançoso; José Carlos Dalmas (Universidade Federal do Paraná, 2018)
Objective: to analyze the care of the child and the use of alternative therapies by mothers in the first 42 days postpartum. Method: quantitative descriptive cross-sectional study carried out in a low-risk public maternity ward, with a home visit at 42 days postpartum, between July 2013 and January 2014, in Londrina-PR. The Fischer Exact and Chi-Square Tests were used considering a 95% confidence interval. Results: among the 357 puerperal women, 50.7% were aged ≤24 years, 69.2% multiparous, 75.4% had ≥8 years of schooling and 49% an income ≥2 minimum salaries. Complementary therapy was predominantly suggested by the grandmothers, used in the child's bath (97=27.2%), on the umbilical stump (143=39.9%), for conjunctivitis (108=81.0%) and for jaundice (56=34.6%). The social class was significant (p=0.005) with age, education, income and use of teas. Conclusion: maternal practices are maintained between generations, some indiscriminately, with it being necessary for the health team to prevent injuries and promote health considering the cultural aspects of the family.